Konstruksi Sanksi bagi Pengusaha yang Tidak Mempekerjakan Pekerja Disabilitas Sesuai Kewajiban Sistem Kuota (RechtJiva, 2024)
Indonesia has adopted the quota system which regulates the minimum number of disabled employees recruited by employer, through Article 53 paragraph (2) of Undang-Undang Republik Indonesia Nomor 8 Tahun 2016 tentang Penyandang Disabilitas. Unfortunately, this regulation has not been effective, evidenced by there are still large number of employers who have not implemented this regulation and the increasing unemployment and the entrepreneurship rate in Indonesia among disabled workers. This allows for inequality of employment opportunities for disabled workers, alongside with their human rights not being protected. Based on these matters, this research raises two research questions, which are (1) what are the implications of the legal vacuum of sanctions for the quota system regulation; and (2) what is the ideal construction of sanctions that can be applied in Indonesia after making comparisons from China and Japan? This research is a normative legal research, with statute, historical, conceptual, and comparative approach. The results of this study are that the legal vacuum condition of sanction for the quota system can create bad precedent for the rule of law visions that Indonesia has, and can lead to a failure to fulfill the principle of labor protection that the labor law has. Furthermore, the sanctions that can be applied are fines/levy and written warnings, with the ULD as the institution authorized to supervise the implementation and impose sanctions, and to support this implementation, technical regulation needs to be issued.